Squat lobsters (Crustacea: Decapoda: Galatheoidea and Chirostyloidea) collected during the TALUD XIV cruise in the Gulf of California, Mexico, and rediscovery of Gastroptychus perarmatus (Haig, 1968) in the eastern Pacific - Hendrickx, Michel E (ZOOTAXA, 2012)
Seven species of squat lobsters were collected during the TALUD XIV cruise in the Gulf of California, Mexico. Gastroptychus perarmatus (Haig, 1968) was collected for the second time since it was described and represents a first record of the genus in the tropical eastern Pacific. Its association with gorgonians is also noted from color pictures taken during a deep-water dive in another cruise in the area. Janetogalathea californiensis (Benedict, 1902) was captured in four sampling stations, in the same area where it has been previously reported. Three species of Munida Leach, 1820 were collected (M. bapensis Hendrickx, 2000, M. mexicana Benedict, 1902, and M. tenella Benedict, 1902). Records of M. bapensis of this cruise combined with additional captures of this species in 2007 in the same area indicate that it is the most abundant deep-water species of squat lobster in the northern part of the central Gulf of California. Among the species of Munida, M. tenella was second in abundance and included specimens much larger than previously known. The single record for M. mexicana fits within the currently known depth and geographical ranges. Only one species of Munidopsis Whiteaves, 1874 (M. depressa Faxon, 1892) was collected, in one of the deeper sampling stations visited during the cruise and its northernmost distribution limit within the Gulf of California is increased by ca two degrees of latitude. The seventh species collected during this survey, Pleuroncodes planipes Stimpson, 1860, is a common inhabitant of the California Current and the Gulf of California.
Keywords: ROV Jason (Remotely Operated Vehicle)